The The Role of Information Systems in Moderate the Impact of Auditor Independence, Audit Complexity, and Time Budget Pressure on Audit Quality - Cykal Pangestu; Ceacilia Srimindarti (Jurnal Economic Resource, 2026)
This study aims to examine the effects of auditor independence, audit complexity, and time budget pressure on audit quality, with information systems serving as a moderating variable. A quantitative research approach was employed in this study. The data were collected from primary sources through questionnaires distributed to auditors working at Public Accounting Firms (PAFs) in Semarang City. The collected data were analyzed using SmartPLS 4 software. The findings reveal that auditor independence has a positive and significant effect on audit quality. However, audit complexity and time budget pressure were found to have no significant impact on audit quality. Furthermore, information systems were not proven to moderate the relationship between either audit complexity or time budget pressure and audit quality.